PREFERENSI KONSUMEN TERHADAP ATRIBUT BUAH PEPAYA (Carica papaya L.) LOKAL DI PASAR TRADISIONAL KOTA BOGOR - Ahar, H Mario; Yoesdiarti, Arti; arsyad, Apendi (JURNAL AGRIBISAINS, 2022)
This study aims to analyze consumer characteristics, determine the process of making purchasing decisions and determine consumer preferences for local papaya attributes in traditional markets in Bogor City. 30 respondents were determined by using accidental sampling. The method of analysis used are descriptive analysis, Multi-attribute Fishbein and Importance Performance Analysis (IPA). The results showed that the characteristics of local Papaya consumers were quite varied, namely gender, age, education, occupation, number of dependents and monthly income. Purchasing decisions are influenced by five factors, namely need recognition, information search, evaluation of alternatives, purchases and outcomes. Consumer preferences can be identified through the attributes found in local papaya fruit such as taste, skin color, size, shape, water content (juiciness), flesh color, flesh thickness, flesh texture and papaya skin texture. The result of Fishbein's Multi-attribute analysis shows that the most influencing attributes for consumer in making purchasing decisions are the color of the meat and the taste attribute of the local Papaya fruit. IPA Matrix Analysis shows that the attributes that must be maintained are taste and color of the meat, and the attributes that need to be developed are the thickness of the meat and the texture of the meat. Keywords: Local Papaya attribute, Fishbein Multi-attribute, IPA Matrix, Consumer Preference, traditional market